Do women top managers help women advance? A panel study using EEO-1 records - Fidan Ana Kurtulus; Donald Tomaskovic-Devey (University of Massachusetts, Department of Economics, 2011)
The goal of this study is to examine whether women in the highest levels of management ranks of firms help reduce barriers to advancement in the workplace faced by women. Using a panel of over 20,000 private-sector firms across all industries and states during 1990-2003 from the U.S. Equal Employment Opportunity Commission, we explore the influence of women in top management on subsequent female representation in lowerlevel managerial positions in U.S. firms. Our key findings show that an increase in the share of female top managers is associated with subsequent increases in the share of women in mid-level management positions within firms, and this result is robust to controlling for firm size, workforce composition, federal contractor status, firm fixed effects, year fixed effects and industry-specific trends. The influence of women in top management positions is stronger among federal contractors, in firms with larger female labor forces, and for white women. We also find that the positive influence of women in top leadership positions on managerial gender diversity diminishes over time, suggesting that women at the top play a positive but transitory role in women's career advancement.
Keywords: J16; J21; J24; J44; J62; J71; J78; J82; M51; 330; Women Managers; Gender Diversity; Discrimination; Mentoring; Promotions; Hiring and Retention; Weibliche Führungskräfte; Weibliche Arbeitskräfte; Erwerbsverlauf; Mittleres Management; USA